2015
DOI: 10.1111/jne.12322
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Attenuates Cocaine‐Seeking Behaviour Independently of Corticosterone Fluctuations

Abstract: The neurosteroid dehydroepiandrosterone (DHEA) is involved in the pathophysiology of several psychiatric disorders, including cocaine addiction. We have previously shown that DHEA attenuates cocaine-seeking behaviour, and also that DHEA decreases corticosterone (CORT) levels in plasma and the prefrontal cortex. Previous studies have found that rats demonstrate cocaine-seeking behaviour only when the level of CORT reaches a minimum threshold. In the present study, we investigated whether the attenuating effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, previous reports showed that repeated DHEAS treatment prevents the development of opioid tolerance without showing an effect on self-administration (70). Additionally, chronic treatment with DHEA has also been shown to reduce cocaine self-administration and reinstatement in rats (71).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, previous reports showed that repeated DHEAS treatment prevents the development of opioid tolerance without showing an effect on self-administration (70). Additionally, chronic treatment with DHEA has also been shown to reduce cocaine self-administration and reinstatement in rats (71).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, previous reports describe a link between DHEAS and the development of opioid tolerance without showing an effect on self-administration 72 . Additionally, chronic treatment with DHEA has also been shown to reduce cocaine self-administration and reinstatement in rats 73 .…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, DHEA administration attenuated cocaine self-administration and decreased cocaine-seeking behaviors. [3][4][5] In humans, high levels of circulatory DHEA sulfate (DHEA-S) were associated with lower relapse rates among individuals addicted to cocaine, 6 as well as with reduced craving in women with alcohol use disorder. 7 Initial attempts to harness these putative effects to reduce relapse rates were unsuccessful, as DHEA administration did not reduce relapse rates or craving among cocaine-dependent participants compared with placebo.…”
mentioning
confidence: 99%
“…In recent years, accumulating evidence from preclinical and clinical studies suggest that administration of dehydroepiandrosterone (DHEA; an endogenous steroid hormone) during rehabilitation may lead to reduced relapse rates in SUD. In rodents, DHEA administration attenuated cocaine self-administration and decreased cocaine-seeking behaviors 3–5 . In humans, high levels of circulatory DHEA sulfate (DHEA-S) were associated with lower relapse rates among individuals addicted to cocaine, 6 as well as with reduced craving in women with alcohol use disorder 7 .…”
mentioning
confidence: 99%